Deltamethrin promotes adipogenesis via AMPKα and ER stress-mediated pathway in 3T3- L1 adipocytes and Caenorhabditis elegans. (December 2019) - Yuan, Li; Lin, Jie; Xu, Yuejia; Peng, Ye; Clark, John M.; Gao, Ruichang; Park, Yeonhwa; Sun, Quancai
Abstract: Previous research has shown that deltamethrin, a Type-II pyrethroid, increases fat accumulation in adipocytes and Caenorhabditis elegans. The underlying mechanisms on how deltamethrin promotes fat accumulation, however, are unknown. The aim of the current study was therefore to determine the possible mechanisms through which deltamethrin increases fat accumulation in mouse 3T3-L1 adipocytes and C. elegans . Deltamethrin (10 μM) significantly increased fat accumulation, and the expression of adipogenic regulators, such as CCAAT/enhancer-binding protein (C/EBPα) and fatty acid synthase (FAS). Deltamethrin significantly decreased the phosphorylation of AMP-activated kinase α (AMPKα), while it increased protein expression of endoplasmic reticulum (ER) stress markers in 3T3-L1 adipocytes and C. elegans . The activation of AMPK with 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) or the inhibition of ER stress with 4-phenylbutyrate (4-PBA) abolished the effects of deltamethrin on adipogenesis. Further study reveals that 4-PBA recovered the decreased AMPK phosphorylation induced by deltamethrin. These results suggest that deltamethrin promotes adipogenesis through an ER stress-AMPKα mediated pathway. Highlights: Deltamethrin promotes adipogenesis in 3T3-L1 adipocytes. Deltamethrin inhibits AMPK phosphorylation and induces ER stress. Deltamethrin promotes adipogenesis through an ER stress-AMPKα mediated pathway.